Methods of limiting selected risk types in the municipal waste incineration plant - Ewa Kubinska-Jabcon; Mariusz Niekurzak (Managerial Economics)
Risk has become one of the most important categories in the global economy. This term belongs to the most popular phenomena in the economy. Decision making is always connected with risk. It is an inseparable part of human history and there are no man’s actions which cannot be associated with it. The notion of risk is universal: it concerns political, economic and social activities. It takes on specific meaning in the space of economic activity: taking risk entails certain financial consequences. Due to this fact, the essence of risk, methods of its evaluation, as well as its management are the topics of a growing number of publications in various scientific fields. The key problem for an entrepreneur is to first determine sources of risk, to assess its size and the influence it may have on the business, and then–to take action in order to minimize this influence. The article analyses dangers in a municipal waste incineration plant. In incineration plants there are various risks but environmental threats, broadly analysed in this article, belong to the most serious ones. Two independent risk analysis methods have been used for this purpose to determine the most serious threats related to environmental risk and options of counteracting them.